Data Analysis and Discussion on the Reliability of the Control Principle of a Sealed Crude Oil Pipeline. Issue 1 (May 2021) - Liu, Junjiang; Feng, Liang; Yang, Dake; Li, Xianghui
Abstract: The current control principles of long-distance crude oil pipeline production and operation are all obtained by theory in the design stage, and lack of on-site actual operation verification. Based on the pigging data of the pipeline put into production in 2017, the simulation software SPS was used to establish the model. Based on the operating data of the pipeline in recent years, the control principles in the preliminary design are checked one by one to verify the reliability of the control principles and propose corresponding improvement suggestions for existing defects. The research results show that the initial control principle of the pipeline has two actual operation defects. One is the low setting value of the water hammer pressure relief valve in the BS station, and the second is the advance protection program error under the failure condition of the MD station; The simulation obtains the set value of the pressure relief limit of each station entry and exit under the principle of advanced protection, and the set value can be adjusted appropriately according to the pressure of the entry and exit pipelines of each station; the response time of each step of the control principle under different fault conditions is simulated, Provide optimization suggestions for some control principles. The above research results can minimize the failure results produced by the failure conditions under the premise of ensuring the effective control principle.